2006
DOI: 10.1108/09596110610681520
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and hospitality marketing: fantasy, feeling and fun

Abstract: PurposeExperiential marketing is arguably marketing's most contemporary orientation, but as with many marketing innovations it has been largely overlooked by those involved in tourism and hospitality marketing and promotion. Whilst in many industries companies have moved away from traditional features and benefits approaches, to putting experiential marketing centre‐stage, marketing in the tourism and hospitality sectors does not appear to have explicitly engaged the theoretical issues involved. This raises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
259
0
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(283 citation statements)
references
References 9 publications
3
259
0
21
Order By: Relevance
“…Nevertheless, the fun element of exploratory play has been highlighted by the participants. Exploratory play includes a fun element in which participants were seeking entertainment from the game; this again proves Williams' (2006) comment that gaming as a new approach that provides an entertaining setting for tourists.…”
Section: '…A Good Way To Get To Know Some Practical Information Aboutmentioning
confidence: 98%
“…Nevertheless, the fun element of exploratory play has been highlighted by the participants. Exploratory play includes a fun element in which participants were seeking entertainment from the game; this again proves Williams' (2006) comment that gaming as a new approach that provides an entertaining setting for tourists.…”
Section: '…A Good Way To Get To Know Some Practical Information Aboutmentioning
confidence: 98%
“…Williams (2010) in a study concluded that tourism development in a region is directly related to the employed marketing strategies which can cause either growth or decline in that region. Moreover, appropriate selection and combination of marketing mix elements can bring about positive results for tourism destinations (Hudson, 2005).…”
Section: Personnelmentioning
confidence: 99%
“…Creating valuable experience to reach the need of consumers and raise customer satisfaction is the key concept of managing experiential marketing. A better experience from services consumed would be more useful to promote consumer's perceptions of value (Williams, 2006). With growing interests towards experiential marketing, both academia and practitioners have made efforts to further comprehend the strategic benefits generated from the so called experiential consumption.…”
Section: Problem Statementmentioning
confidence: 99%